2021
DOI: 10.1088/1755-1315/893/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Lightning Analysis Over North Sulawesi in 2019 - 2020

Abstract: This study aimed to analyze the spatial and temporal lightning distribution in North Sulawesi. The general meteorological condition of North Sulawesi has also been considered to identify the cause of the lightning occurrence. Lightning activity over North Sulawesi has been investigated using lightning data from Winangun Geophysical Station during 2019-2020. The result shows that in the land area of North Sulawesi, the highest lightning density occurred in the Tomohon regions due to its topographical features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Therefore, high humidity has a relationship to pulmonary TB transmission because it plays a role in the growth of tuberculosis bacteria (H. H.D. Lasari, Medyna, Fadillah, Rosadi, & Fakhriadi, 2023). The results of research by Nurdiana et al (2018) showed that there was a significant relationship between humidity and the transmission of pulmonary TB in family members with a P-value = 0,017 (p < 0,05) (Nurdiana, Haidah, & Nerawati, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, high humidity has a relationship to pulmonary TB transmission because it plays a role in the growth of tuberculosis bacteria (H. H.D. Lasari, Medyna, Fadillah, Rosadi, & Fakhriadi, 2023). The results of research by Nurdiana et al (2018) showed that there was a significant relationship between humidity and the transmission of pulmonary TB in family members with a P-value = 0,017 (p < 0,05) (Nurdiana, Haidah, & Nerawati, 2018).…”
Section: Resultsmentioning
confidence: 99%